Inhibition Mechanism of Cinnamomum burmannii Leaf Essential Oil Against Aspergillus flavus and Aflatoxins - Huanyan Liang; Feifei Lv; Mengting Xian; Chenghua Luo; Lei Zhang; Meihua Yang; Qian Li; Xiangsheng Zhao (Foods)
This investigation evaluates the comparative efficacy of Cinnamomum burmannii leaf essential oil (YXYO) and its main active ingredients as a novel preservative to protect stored food commodities from fungal infestations, aflatoxin B1 (AFB1) contamination caused by Aspergillus flavus. Morphological observations utilizing SEM and TEM revealed significant alterations in treated samples, alongside a decrease in ergosterol content and a dose-dependent disruption of the antioxidant system and energy system. Transcriptomic analysis suggested that differentially expressed genes were predominantly associated with spore growth, the cell wall, the cell membrane, oxidative stress, energy metabolism, and aflatoxin biosynthesis. Solid-phase microextraction–gas chromatography–mass spectrometry (SPME-GC-MS) identified ten active ingredients in YXYO, including borneol, α-terpineol, terpinen-4-ol, etc. Moreover, an effective inhibition of A. flavus infection in peanuts was observed with the application of 30 μL/disc of YXYO and a blend of its active compounds.